PENGARUH INTELECTUAL CAPITAL DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Sektor Industri Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2017 – Tahun 2020) - Mulia Rahmah, S. Kom., M.Si.; Retno Dwidjayanti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
To test and analyze the influence of Intellectual Capital and Corporate Social Responsibility partially on the Performance of Manufacturing Companies in the Food and Beverage Industry Sector Listed on the Indonesia Stock Exchange for the 2017-2020 Period.The analytical method used in this study namely by using descriptive statistical methods and multiple regression then using classical assumption and hypothesis testing using T test, F test and R² test, sampling using purposive sampling method with a population of 26 from the population obtained 15 samples. The results showed that partially or in accordance with. the results of the T test, that Intellectual Capital and CSR have a significant effect on the performance of the Study Company in Manufacturing Companies in the Food and Beverage Industry Sector Listed on the Indonesia Stock Exchange for the 2017-2020 period.